Beautiful people et la blessure secrète - Bardagil, Miquel; Chéronnet, Clémentine; Pierron, Nathalie; Vigourous, Sophie; FRAC, Nord-Pas de Calais (Nord Pas de Calais : FRAC, 2007)
Ben ; Boltanski, Christian ; Boulanger, Christophe ; Burgin, Victor ; Closky, Claude ; De Bruyckere, Berlinde ; De Rijke, Jeroen ; De Rooij, Willem ; Fabre, Jan ; Feldmann, Hans-Peter ; Gage, Jenny ; Goldstein, Jack ; Jones, Sarah ; Kolar, Jiri ; Koudelka, Josef ; et al.
Collection FRAC Nord-Pas de Calais
kunstcatalogus